Effect of process parameter variations on threshold voltage in 45nm NMOS device - Salehuddin F.; Ahmad I.; Hamid F.A.; Zaharim A. (2023)
Taguchi method was used to optimize of the effect process parameter variations on threshold voltage in 45nm NMOS device. In this paper, there are four process parameters (factors) were used, which are Halo Implantation, Source/Drain (S/D) Implantation, Oxide Growth Temperature and Silicide Anneal temperature. The virtual fabrication of the devices was performed by using ATHENA module. While the electrical characterization of the devices was implemented by using ATLAS module. These two modules were combined with Taguchi method to aid in design and optimizer the process parameters. Threshold voltage (VTH) results were used as the evaluation variables. The results were then subjected to the Taguchi method to determine the optimal process parameters and to produce predicted values. The predicted values of the process parameters were then successfully verified with ATHENA and ATLAS's simulator. In this research, oxide growth temperature was identified as one of the process parameters that has the strongest effect on the response characteristics. While the S/D Implantation was identified as adjustment factor to get the nominal values of threshold voltage for NMOS device equal to 0.15V. 2010 IEEE.